URGENSI KOMUNIKASI EFEKTIF DALAM PUBLIC RELATIONS - Salsabila, Julia; Juliadrianti, Marcha; Luqyana, Khairunnisa; Kadri, Hanif Al; Setiawati, Merika (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2023)
Effective communication has a crucial role in the realm of public relations. Communication effectiveness is realized when the message conveyed by the communicator is appropriate and identical to the message received by the communicant, without any reduction or addition of words that might give rise to wrong interpretations. In the context of public relations, effective communication has a major impact on the quality of relations between an organization and its public. A public relations practitioner's ability to communicate effectively has the potential to form a positive image of the organization. This article is the result of a literature review detailing aspects of communication and public relations, with the aim of realizing effective communication in the context of public relations. Effective communication strategies in public relations are directed at establishing positive relationships with the public as well as aspirations to create a positive view of the organization among the public. Therefore, it is important for a public relations practitioner to have superior communication skills.